The Effect of Resistance Band Leg Press and Resistance Band Lying Leg Press on Leg Muscle Power Shooting Results in Athletes Aged 15-16 Years Ssb Sejati Pratama Medan Johor in 2024 - SK, Anugrah Abta (Jurnal Pendidikan Jasmani (JPJ), 2025)
This study aims to determine the effect of Resistance band leg press and Resistance band lie leg press exercises on the power of shooting range muscles of SSB Sejati Pratama students aged 15-16 years. The method used is an experiment with a one group pretest-posttest design. The population used in this study were all students of the Sejati Pratama Football School (SSB) totaling 35 people and a sample of 10 athletes with a sampling technique using a purposive sampling technique. The data collection technique used is by taking pre-test, treatment and post-test. Hypothesis testing of 12.256 and ttable 1.833 then (tcount> ttable), so it can be seen that there is a significant effect of providing variations of Resistance band leg press and resistance band lie leg press exercises on increasing muscle power including SSB Sejati Pratama students aged 15-16 years. From the Shooting data that has been done, it is known that the tcount value of the hypothesis is 7.36 and ttable 1.833 then (tcount> ttable), so it can be seen that there is a significant effect of providing Resistance band leg press and resistance band lie leg press exercises on increasing Shooting results of SSB Sejati Pratama students aged 15-16 years. Therefore, there is an Effect of Resistance band leg press and resistance band lie leg press Exercises on Increasing Muscle Power in Shooting Results in Students Aged 15-16 SSB Sejati Pratama in 2024.